2020
DOI: 10.1111/aos.14532
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Retinopathy of Prematurity Activity Scale (ROP‐ActS) using retrospective clinical data

Abstract: The International Neonatal Consortium recently published a proposed retinopathy of prematurity (ROP) activity scale intended for use in clinical trials after validation. The aim of this study was to validate the ROP activity scale (ROP-ActS) in a ROP screened cohort with protocol based collected data by evaluating the ability of the ROP-Act scores to predict ROP treatment. In addition, we aimed to evaluate the scale's sensitivity characteristic of disease severity by studying association with gestational age (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It was proposed to switch scores 3 (zone II stage 1) and 5 (zone III stage 3). 12 In the current study, the percentage of infants with score 3 that finally led to ROP treatment was 24%, and for score 5 was 22%, compared with 33% and 14% in the retrospective study. The decision for switching the scores 3 and 5 would not be as substantiated in this study as in the previous one.…”
Section: Discussionmentioning
confidence: 43%
See 3 more Smart Citations
“…It was proposed to switch scores 3 (zone II stage 1) and 5 (zone III stage 3). 12 In the current study, the percentage of infants with score 3 that finally led to ROP treatment was 24%, and for score 5 was 22%, compared with 33% and 14% in the retrospective study. The decision for switching the scores 3 and 5 would not be as substantiated in this study as in the previous one.…”
Section: Discussionmentioning
confidence: 43%
“…In the retrospective validation study of ROP-ActS, including 535 infants and 3324 ROP screening examinations, we concluded that the original ROP-ActS was relatively well ordered against the short-term outcome, treated ROP. It was proposed to switch scores 3 (zone II stage 1) and 5 (zone III stage 3) 12. In the current study, the percentage of infants with score 3 that finally led to ROP treatment was 24%, and for score 5 was 22%, compared with 33% and 14% in the retrospective study.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Beyond ROP treatment and prevention, we will see a new ROP nomenclature, ICROP 3, being published in 2021 taking into account the new forms of the disease we see after anti-VEGF therapy (namely regression and reactivation). We have in recent months also seen important progress in diagnosing and grading ROP with the help of artificial intelligence [25,26] and we have seen ROP severity scores being developed to better compare ROP disease severity during the course of an individual disease [27,28].…”
Section: Introduction and Study Overviewmentioning
confidence: 99%